Colletotrichum siamense causing anthracnose in Bauhinia forficata subsp. pruinosa in Argentina - Larran, Silvina (2015)
Bauhinia forficata subsp. pruinosa is a common perennial tree species native to South America that belongs to the Fabaceae. In December 2010 and 2011, plants from a nursery located in the province of Buenos Aires, Argentina presented typical symptoms of anthracnose.We isolated from the lesions of diseased leaves a fungus that based on morphological as well as the ITS (KC132841) and β-tubulin sequences (KJ829534) was identified as Colletotrichum siamense. After 12 days leaves inoculated with the fungal spore suspension developed lesions similar to those observed in natural infections. The fungus was then re-isolated fulfilling Koch’s Postulates. To our knowledge, this is the first report of Colletotrichum siamense causing anthracnose in Bauhinia forficata subsp. pruinosa in Argentina.